Model Pengembangan Usaha Kecil Menengah Berbasis Potensi Ekonomi Masyarakat - Taufik, Mokhamad; Hartono, Hartono (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2011)
Shackles of poverty that the people of Indonesia is not a new problem so as to not be a problem anymore. But the condition is getting worse by the economic crisis that began in mid 1997 and then followed by a multi-dimensional crisis. The number of poor people who previously has successfully suppressed about 11%, allegedly by CPM could be around 24% at the peak of the crisis of 1998 due to massive layoffs of the foot-loose industry sector. In the gloom of the economic crisis, which was originally quite large industry contributes greatly to the economic growth rate, but when the crisis one by one collapse. In contrast to micro, small and medium enterprises, has been proven at the time of the crisis can provide a significant contribution to economic growth. From the studies have been done, the problems of SMEs in the development model Lumajang is through: the development and coaching to small and medium enterprises is one solution to overcome the problem of economic inequality and poverty in the City Lumajang; model clustering is a pattern of coaching centers that can improve competitiveness and productivity of small and menengah.dan in the future to be the leading sector in the City Lumajang poverty alleviation; pattern precise and comprehensive guidance for small and medium enterprises is a coaching model clustering centers by building partnerships between SMEs, the Government District, traditional markets and modern market. In an effort to overcome the problems of small and medium enterprise development, the need for emphasis of collaborative action from various parties, namely through: the development and building of small and medium businesses need to get serious attention from the Government, in the form of stimulus policies and a conducive and productive business building small and medium-use centers clustering model requires the government's role to memfasilitasasi involvement of various parties that influence tissue integration of SMEs with large insdustri involved as a partner and expansion of market access.